'Race' and inequality in postcolonial urban settings; Examples from Peru, Jamaica, and Indonesia - Nas, Peter J.M.; Jaffe, Rivke; Algoed, Line (UI Scholars Hub, 2009)
In this essay we present three case studies of Peru, Jamaica and Indonesia to illustrate the use of the concept of race in daily life in relation to labour, popular culture and beauty respectively. These cases demonstrate how the use of the concept of race changes in the transition from a colonial into a postcolonial setting, depending on the role of the state and nation building. In Peru, we see a clear continuation of racialized thinking; thinking and speaking in terms of 'race' is still the norm. In Jamaica we find a process of inversion: the concept of race is maintained as a frame of societal analysis, but blackness is revalidated and has become a prerequisite for national and cultural belonging. In Indonesia racialized categorizations have disappeared almost completely as 'race' has become subjected to the development rhetoric, which just allows limited space for ethnic manifestations. However, discrimination on other rhetorical basis, such as non-citizenship, remains.